2020
DOI: 10.1111/1758-5899.12856
|View full text |Cite
|
Sign up to set email alerts
|

US Strategies of Institutional Adaptation in the Face of Hegemonic Decline

Abstract: How do shifts in the global distribution of power affect the US' preferences for institutionalized cooperation? This article explains why and when the power shift creates incentives for the US to move cooperation out of universal multilateral institutions, such as the WTO, and into exclusive multilateral institutions where it seeks to create a leading consensus among a select group of 'like-minded' states. An agreement reached within the subgroup imposes costs on those excluded from the deal. This increases th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Wu et al ( 2008 ) described firm-level competitiveness as the ability of the firm to optimally deploy and mobilize its assets and capabilities to derive competitive advantage in the market. The onset of COVID-19 pandemic and its aftermath resulting in nations increasingly looking to reduce external country reliance in strategic areas (Koleson, 2020 ; Viola, 2020 ) also increase the onus on how technology-based startups can help increase India’s competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al ( 2008 ) described firm-level competitiveness as the ability of the firm to optimally deploy and mobilize its assets and capabilities to derive competitive advantage in the market. The onset of COVID-19 pandemic and its aftermath resulting in nations increasingly looking to reduce external country reliance in strategic areas (Koleson, 2020 ; Viola, 2020 ) also increase the onus on how technology-based startups can help increase India’s competitiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Russia’s leadership has been essential for launching BRICS, and China’s power advantage enabled it to influence other members to implement its global economic governance reform agenda (Hooijmaaijers, 2021; Katada et al, 2017). The US is already responding to BRICS by engaging ‘like-minded states’ to work around institutions within which BRICS can potentially block US initiatives (Viola, 2020). Vezirgiannidou (2013) frames US support for a permanent seat for India on the UNSC, but silence on one for Brazil, as partly reflecting an effort to ‘split the BRICS’ unity’.…”
Section: Brics Convergence and Counter-hegemonic Potentialmentioning
confidence: 99%
“…The US’ withdrawal from the WHO in the middle of the pandemic, though reversed in January 2021 with the change in presidency, showed that multilateral institutions designed to address global issues are fragile and that they ultimately depend on the will of the largest geopolitical powers to lead international coordination and provide funding and technical expertise. Some scholars have argued that multilateralism – “the institutionalized cooperation […] on the basis of generalized rules and principles, has been a core characteristic of the modern international system” (Viola, 2020 : 30) – was already in decline before the pandemic (Acharya, 2016 ). However, the response to the previous recession that affected a large share of the world economy, namely the 2008–2009 financial crisis, featured a high degree of international policy coordination and a crucial role for both global and regional multilateral institutions such as the IMF and the European Central Bank (International Monetary Fund, 2010 ).…”
Section: The Enduring Consequences Of the Pandemic That Will Compromise Globalizationmentioning
confidence: 99%